TENIS U CRNOJ GORI S POSEBNIM OSVRTOM NA METODOLOGIJU RADA NA TENISKOM ZIDU - Dimitrije Rašović; Ivana Rašović (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2007)
Newest research by the author of this work, Dimitrije Rašović, shows that the founder of tennis in Montenegro is for shure Momčilo Tapavica, winner of the bronze medal at the First Olympic Games in Athenes 1896. All hits against the wall are executed while moving forward making the wall practice the basis of the contemporary offensive tennis play. On the court the player at the other side of the net will be defeated with carefully planned tactics, physical readiness and perfectly executed technique. Every tennis player regardless of rank or experience, should remember that the tennis wall stands somewhere in the corner of the tennis court. That is the strongest tennis "opponent" and an invaluable "instructor" in the creation, training and development of any recreational or professional tennis player